The outcome and risk factors associated with central and peripheral nervous system involvement in hospitalized COVID-19 patients: a retrospective cohort study - Hanganu, Andreea Raluca; Niculae, Cristian-Mihail; Dulămea, Adriana Octaviana; Moisă, Emanuel; Constantin, Rareș; Neagu, Georgiana; Hristea, Adriana (Frontiers in Neurology, 2024)
Introduction: SARS-CoV-2 infection can affect any organ, including both the central (CNS) and peripheral nervous system (PNS). The aim of this study was to explore the outcome and risk factors associated with the involvement of either CNS or PNS in a cohort of hospitalized COVID-19 patients. Methods: We performed a retrospective observational cohort study of hospitalized adult patients with COVID-19, between May 2020 and December 2022, presenting with new onset neurological disabilities any time after admission. Results: We included 115 patients, 72 with CNS manifestations and 43 with PNS involvement. The CNS manifestations were COVID-19 associated encephalopathy, headache, neurovascular events and seizures in 80.5%, 43%, 31.9% and 11.1% patients respectively. The neurovascular events were ischemic stroke in 17 (23.6%) patients, hemorrhagic stroke in six (8.3%) patients, venous thrombosis in one (1.4%) patient and subarachnoid hemorrhage in one (1.4%) patient. Cranial nerves involvement was the most frequent PNS manifestation in 34 (79%) cases, followed by mononeuritis in five (11.6%) patients and polyneuropathy in four (9.3%) patients. The affected cranial nerves were the vestibulocochlear nerve in 26 (60.5%) patients, the olfactory nerve in 24 (55.8%) patients, the oculomotor nerves in five (11.6%) patients and the facial nerve in one (2.3%) patient. Two patients (9.3%) presented with polyneuritis cranialis. Older age (HR = 1.02, 95% CI: 1.003-1.037, p=.01), COVID severity (HR = 2.53, 95% CI: 1.42-4.5, p=.002), ischemic cardiac disease (HR = 2.42, 95% CI: 1.05-5.6, p=.03) and increased D-dimers (HR = 1.00, 95% CI: 1.00-1.00, p=.02) were independently associated with the development of CNS manifestations. The factors associated with in-hospital mortality and were age (HR = 1.059,